2015
DOI: 10.1159/000375360
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Diagnoses of Adenocarcinoma in situ of the Cervix: Common Misdiagnoses

Abstract: Objective: In routine screening, glandular lesions have high false-negative and false-positive rates. Our study sought to improve the cytological diagnoses and differentiation of glandular lesions. Study Design: A total of 24 cytology slides were retrospectively reviewed. Among these slides, 15 were confirmed via histology to have varying amounts of adenocarcinoma in situ (AIS) components. The other 9 cytology slides exhibited AIS mimics that had been originally considered to be AIS or atypical glandular cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Previous studies have identified the pitfalls of the AIS cytologic diagnosis, also its suboptimal accuracy and low levels of interobserver agreement [30][31][32]. Some authors have also reported that many AIS lesions could be interpreted as AGC, AGC-FN, ADC, or squamous intraepithelial lesions in cervical cytology [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified the pitfalls of the AIS cytologic diagnosis, also its suboptimal accuracy and low levels of interobserver agreement [30][31][32]. Some authors have also reported that many AIS lesions could be interpreted as AGC, AGC-FN, ADC, or squamous intraepithelial lesions in cervical cytology [32,33].…”
Section: Discussionmentioning
confidence: 99%